Re-Layout of Service Room to Overcome Waiting Time of Finished Drug Services in Outpatient Pharmacy of dr. Iskak General Hospital Tulungagung - Yulianto, Wahyu; Sujianto, Sujianto; Hariyanti, Tita (Fakultas Kedokteran Universitas Brawijaya, 2021)
ABSTRACTÂ Background: The minimum standard waiting time for finished drug services in an outpatient pharmacy depot is less than 30 minutes. However, the implementation of standard waiting time for finished drug services at dr. Iskak General Hospital Tulungagung is still above the standard that is 69.83 minutes. This study aimed to analyze the factors causing the long waiting time for finished drug services in outpatient pharmacy and to find solutions to overcome the long waiting time.Methods:Â This research used a qualitative method, and the data collection was carried out by observation, interviews, and focus group discussions (FGD).Results:Â The observation results show that the actual time required to complete one prescription was 11 minutes and 50 seconds. The roots of the problem identified were the accumulation of prescriptions in the administration of the outpatient pharmacy depot, inefficient service layout, and low utilization of information technology. The results of the FGD illustrated the alternative solutions to the regulation of prescription arrival by setting the doctor schedule, the application of electronic prescriptions, and spatial arrangements for outpatient pharmacy depots.Conclution: This study concluded that ineffective service layout is a very influential factor in the waiting time for finished drug services in the pharmacy. Arrangement of the outpatient pharmacy service layout can reduce the waiting time for drug services into less than 30 minutes.Keywords: waiting time, focus group discussion, re-layout, pharmacy